2012
DOI: 10.1016/j.tics.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the striatum to learning, motivation, and performance: an associative account

Abstract: It has long been recognized that the striatum is composed of distinct functional sub-units that are part of multiple cortico-striatal-thalamic circuits. Contemporary research has focused on the contribution of striatal sub-regions to three main phenomena: learning of associations between stimuli, actions and rewards; selection between competing response alternatives; and motivational modulation of motor behavior. Recent proposals have argued for a functional division of the striatum along these lines, attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
203
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(219 citation statements)
references
References 100 publications
(160 reference statements)
7
203
0
Order By: Relevance
“…In other words, the increased BOLD signal in DLS and DMS correlating with increased trialwise probability of reward receipt may reflect either model-free or model-based Pavlovian learning (or both). This interpretation is in line with previous findings that DLS codes model-free, whereas DMS processes model-based, instrumental learning (Liljeholm and O'Doherty 2012;Wunderlich et al 2012). It suggests that the neural computation underlying Pavlovian learning may be similar to that of instrumental learning (Dayan and Berridge 2014).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In other words, the increased BOLD signal in DLS and DMS correlating with increased trialwise probability of reward receipt may reflect either model-free or model-based Pavlovian learning (or both). This interpretation is in line with previous findings that DLS codes model-free, whereas DMS processes model-based, instrumental learning (Liljeholm and O'Doherty 2012;Wunderlich et al 2012). It suggests that the neural computation underlying Pavlovian learning may be similar to that of instrumental learning (Dayan and Berridge 2014).…”
supporting
confidence: 92%
“…Surprisingly however, recent lesion and functional magnetic resonance imaging (fMRI) studies suggest that dorsomedial striatum (DMS; for a brief anatomic introduction of striatum, see Fig. 1) is implicated in model-based instrumental learning (Liljeholm and O'Doherty 2012;Wunderlich et al 2012). What makes the picture more complex is that, using a task dissociating the two types of learning, Daw et al (2011) found that ventral striatum (VS) signal encodes both model-free and model-based instrumental learning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the declarative memory system involves the MTL cooperating with the ventromedial prefrontal cortex (Preston and Eichenbaum, 2013), and enables instance learning, the extraction and application of underlying associative or categorical rules (generalization) to new instances, as well as retrieval of ensuing episodic and semantic memories (Hoscheidt et al, 2010). The second non-declarative learning system allows for rapid, feedback-based learning of patterns predicting reward, via the recruitment of the basal ganglia (Delgado and Dickerson, 2012;Poldrack and Foerde, 2008), and is essential for habit learning (Liljeholm and O'Doherty, 2012;Schwabe and Wolf, 2013;Smith and Graybiel, 2013). Both systems are capable of some form of associative learning and generalization, and increasing evidence points toward the collaboration between them in post-encoding episodic memory registration (Ben-Yakov and Dudai, 2011) and retrieval (Scimeca and Badre, 2012).…”
Section: Declarative Memorymentioning
confidence: 99%
“…As the BG are involved in both reinforcement learning and motivation, 9 lesions may have influenced these processes separately or together. A task permitting dissociation of learning from reward sensitivity, or the examination of the ).…”
Section: Resultsmentioning
confidence: 99%